Happiness Therapy and Emotion Regulation for Early Married Couples Facing Emotional Abuse in the Marelan Area - Afriani, Miskah; Chairunnisa, Milna; Saputri, Mega (RIRAI Publisher, 2024)
ABSTRACT Conflicts were Indonesia's most common causes of divorce in 2023, accounting for 251,828 instances, or 61.67% of total divorce cases. Emotional abuse is a significant problem that can affect any relationship, even young married. A research analysis discovered that counseling and therapies were beneficial in mitigating the detrimental impacts of emotional abuse. The aim of the study is happiness therapy and emotion regulation for early marriage couples. This study was a pre-experimental approach. The study's statistical population consisted of 8 couples selected as a sample by purposive and voluntary sampling. Then, the happiness therapy and emotional regulation therapy protocol by Seligman. The researcher implemented the therapy in three sessions of 60-90 minutes, Then, the approaches were performed in pairs for happiness therapy and emotional regulation therapy for each couple with a month follow-up. Data were collected via semi-structured interviews. The study's findings suggest that, on a qualitative level, the informants' pre-therapy emotions were melancholy because of the emotionally abusive home environments they frequently experienced. Several informants felt disheartened and helpless to change their circumstances. Behavioral improvements were noted concerning happiness and emotional regulation. These included modifications to behaviors related to relying on calmness, communicating happiness without expressing emotion, and viewing happiness as a marriage obligation. This study can conclude that as couples learn to navigate their relationship dynamics with empathy and understanding, create a resilient partnership capable of weathering challenges without resorting to harmful behaviors. By prioritizing happiness therapy principles, couples can cultivate a harmonious union characterized by mutual respect and love.